2017
DOI: 10.4236/ojanes.2017.72004
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Effective Systemic Lidocaine Dosage on the Expression of HMGB1 mRNA on Mice with Sterile Musculoskeletal Injury

Abstract: A severe injury can trigger an inflammation response and excessive response can cause multiple organ failure. HMGB1 is an early inflammation mediator in sterile injury and a late inflammation mediator in infection. It is an impor-tant mediator in severe sepsis and always associated with the severity of organ failure. Previous studies showed that the administration of systemic lidocaine could inhibit the expression of HMGB1 on septic mice with musculoskeletal injury. Nine male adult Balb/c mice were grouped by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Intravenously administered lidocaine can be used for transcription inhibition of HMGB1 mRNA expression and TLR4 protein translation in sterile inflammation of mice [ 4 ]. In the sublining layer of joints in rheumatoid arthritis and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenously administered lidocaine can be used for transcription inhibition of HMGB1 mRNA expression and TLR4 protein translation in sterile inflammation of mice [ 4 ]. In the sublining layer of joints in rheumatoid arthritis and osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that HMGB1 has molecular impact in Pathogen-Associated Molecular Patterns (PAMPs) in infection and Damage-Associated Molecular Patterns (DAMPs) in injury [ 3 ]. Previous studies showed that HMGB1 has involved in molecular mechanisms of systemic lidocaine treatment for closed fracture musculoskeletal injury in animal model [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our result shows that intravenous administration of 2 mg/kg lidocaine effectively inhibited transcription of HMGB1 mRNA expression in BALB/c mice with a closed fracture musculoskeletal injury. [ 20 ] The increased HMGB1 protein levels decreased from 1819.66 ± 239.50 to 417.00 ± 222.86 after lidocaine therapy for 24 h, showing that intravenous administration of 2 mg/kg of lidocaine was effective in suppressing the translation of HMGB1 protein content in BALB/c mice with a closed fracture musculoskeletal injury. [ 20 21 22 ] The initial HMGB1 protein level was slightly higher than the level after 24 h of systemic lidocaine therapy, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that 2 mg/kgBW lidocaine administration inhibits transcription of HMGB1 mRNA expression and translation of TLR4 protein in sterile injury BALB/c mice with sterile injury. 16,17 Previously, Hollmann MW et al have shown that amide groups local anesthesia inhibited release of inflammatory mediators leukotrin B4 and interleukin-1 from human neutrophils and monocytes. 8 In a previous reasearch, Wang HL et al demonstrated that administration of systemic lidocaine inhibits release of HMGB1 septic mice which induced with lypopolysaccharide 10 and transcription of mRNA HMGB1 in patients during histerectomy.…”
Section: Discussionmentioning
confidence: 99%